Efeitos do PECS associado ao Point-of-view Video Modeling na comunicação de crianças com Transtorno do Espectro Autista - Rodrigues, Viviane (Universidade Federal de São Carlos, 2018)
This study aimed to analyze the effects of the Picture Exchange Communication System (PECS) associated to Point-of-view Video Modeling (POVM) on the performance of the communicative skills of children diagnosed with Autistic Spectrum Disorder (ASD) and Complex Communication Needs, as well as involve the parents, teachers and trainees of these children throughout the process. The specific objectives for the primary participants with ASD were: to analyze the performance during the intervention, to ascertain the level of independence, to monitor the vocabulary, to demonstrate the communication skills; for participants parents, trainees and teachers: to analyze the training given to the communication partners about the intervention, evaluate the performance of the communication partners during the PECS and POVM implementation, to develop a PECS Maintenance Guide for communication partners; to verify the intervention social validity. Three children with ASD with ages ranging from four to six years old and their respective parents, trainees and teachers, participated in the study. For data collection, the following instruments were used: Vocabulary selection worksheet; Participant Performance Record Sheet; Vocabulary Registration Sheet; Communication Skills Questionnaire; Questionnaire referring to the contents taught in the Theoretical Preparatory Course; Communication partners performance record sheet; Social Validity Questionnaire. The experimental design of multiple baseline design by subjects combined with the alternate treatments was used, PECS was associated to POVM being the independent variable and the communication skills were the dependent variable. Data were analyzed considering aspects such as: participants' performance percentage of correct responses; level of independence; vocabulary number expressed; percentage of participants' communication skills responses before and after the intervention; average percentage of responses before and after the theoretical preparatory course; correct performance percentage of communication partners. The results showed that from the beginning of the intervention, the data levels and trends changed, all the participants obtained the criterion, reaching 100% non-overlapping. In all phases of PECS associated to POVM the participants had an average percentage above 90%. As for the vocabulary, two participants performed the communication using figure and speech, while only a participant made the communication through the figures. There were gains in communication skills, even those that were not foreseen. The participants parents, trainees and teachers presented a change in the knowledge taught in the Preparatory Theoretical Course, in which the pre-test average was 70% and in the post-test 87%. Regarding the performance as communication partners they obtained the average of 69% correct answers at the beginning, in the end, they obtained an average of 91% of correctness. The PECS Maintenance Guide has been handed out to parents, trainees and teachers in order to assist them in meeting the needs of the PECS user. The study was considered as socially valid by the responsible, trainees and teachers. It was concluded that the participants with ASD indicated a change after the intervention, comparing baseline condition with intervention and follow-up, demonstrating a possibility in Augmentative and Alternative Communication for children with ASD.
Effects of the PECS associated with the Point-Of-view Video Modeling in the communication of children with Autism Spectrum Disorder
Keywords: Educação especial; Comunicação suplementar e alternativa; Transtorno do espectro autista; Sistema de comunicação por troca de figuras; Modelagem em vídeo; Special education; Augmentative and alternative communication; Autistic spectrum disorder; Picture exchange communication system; Video modeling; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO